Analysis of Mathematics Problem Solving Ability of Junior High School Students in Solving Problems in Online Learning - Rick Hunter Simanungkalit; Renita Br Peranginangin (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determine the mathematical problem solving ability of students in solving story problems with online learning. The method in this study used a qualitative descriptive research method. The results showed that there were differences in the ability to identify the elements that were known and asked, there were differences in the ability to choose and apply strategies or problem solving procedures and there were differences in the ability to examine and explain the results or answers according to problems between students with high, medium mathematical problem solving abilities. and low. There are 43% of students who have been able to follow and adapt online learning while 57% of other students have difficulty understanding the material being taught. There are 60.86% of students who have a high enough enthusiasm in online learning (online) but 39.13% of students are not happy if learning mathematics is done online due to factors that influence it such as technical constraints. There are 73.91% of students with a positive response to the problem of mathematical problem solving ability even though the learning is carried out online and 26.08% of students with a negative response.